Binary System of Diethyl Ether with Chloro-alkanes, Benzene, Toluene and Xylene - N. Modi, Ashvin (Asian Journal of Chemistry, 2010)
Spectral absorbance of dye indicator for binary mixtures ofdiethyl ether with chloro-alkanes, benzene, toluene or xyleneindicates molecular interactions among these liquids. Some of themindicate higher peak absorbance and few cases lower absorbance.An interpretation has been offered.